A closer look at the light-induced changes in the mechanical properties of azobenzene-containing polymers by statistical nanoindentation. Issue 42 (2nd October 2015) - Sorelli, Luca; Fabbri, Filippo; Frech-Baronet, Jessy; Vu, Anh-Duc; Fafard, Mario; Gacoin, Thierry; Lahlil, Khalid; Martinelli, Lucio; Lassailly, Yves; Peretti, Jacques
Abstract : Statistical instrumented nanoindentation measurements demonstrate the large decrease in the viscosity of azo-polymer thin films under light excitation. Abstract : The mechanical properties of azobenzene-containing polymer films are statistically measured by instrumented nanoindentation experiments in the dark and under illumination in the absorption band of the azobenzene molecules. The material is obtained from a commercial PMMA compound grafted with Disperse Red 1 (DR1) azobenzene derivative. In the dark, DR1 molecules remain in the stable trans isomer state while, under illumination, they undergo photoisomerisation cycling and form a photo-stationary equilibrium between cis and trans isomers. This material is known to exhibit light-induced deformation phenomena related to the photoisomerization cycling of the DR1 units. Statistical loading/unloading tests performed in the tens of μN load range reveal a significant change in the mechanical properties of the film under light excitation. The material hardness and irreversible viscosity are seen to decrease, while the creep coefficient value increases, indicating a significant reinforcement of the viscoplastic response of the film under illumination. Moreover, creep experiments performed at a constant load show striking dissipative effects when light is turned on and also, surprisingly, when light is turned off. These features are supposedly related to the transient changes in the balance between the cis and trans isomer populations.